ESTABLISHING THE DISTRIBUTION OF WEST NILE VIRUS OUTBREAKS IN ROMANIA BY USING CLIMATIC SCENARIOS - Liviu Dan MIRON; Larisa Maria IVĂNESCU; Raluca MÎNDRU; Simona MĂTIUȚ; Gabriela-Victoria MARTINESCU; Ilie BODALE (Journal of Applied Life Sciences and Environment)
West Nile virus (WNV) is a re-emerging zoonotic pathogen that represents a threat to both human and animal health. It is difficult to estimate the impact of WNV in the future, although many of the climatic factors influencing its spread have been identified. In this study, we used bioclimatic indices to estimate those periods that favour the growth of vector mosquito populations and the incubation periods for the virus. To this end, we studied the climatic changes in the Romanian regions where cases of WN infection have been reported. Simulations were carried out for 2100 based on long-term scenarios. Identifying the bioclimatic conditions which can cause WNV outbreaks in Romania is necessary to anticipate and thereby prevent future epidemics. However, no extraordinary weather events were registered in the years with WNV outbreaks which could explain such a high number of cases. Thus, in the High Scenario (which will occur if actions to control (GHG) gas emissions are not taken or implemented effectively), the hatching period is extended until November, with the risk that adult mosquitoes are active throughout the year, ensuring a high survival rate of the virus within mosquitoes. In addition, in the High Scenario, the transmission period of the virus is extended from April to October, which underlines the need to establish monitoring and control programmes for both mosquito populations and the spread of the virus among the animal and human populations.